From the gut to the brain, mechanisms and clinical applications of γ-aminobutyric acid (GABA) on the treatment of anxiety and insomnia - Jiang, Chengji; Chen, You; Sun, Tao (Frontiers in Neuroscience, 2025)
Anxiety and insomnia are prevalent global mood disorders, and affect approximately 4 and 10 out of every 100 individuals, respectively. Common abnormal brain activity and altered neural circuitries are detected in patients with anxiety disorders and insomnia, suggesting overlapping pathogenesis in these two disorders. Promisingly, GABA from dietary supplements and GABA produced by gut microbiota have shown significant treatment effects in anxiety and insomnia. This review summarizes neurological mechanisms causing anxiety and insomnia, reveals cellular pathways transferring GABA from the gut to the brain, and delivers the therapeutic potential of gut derived GABA for anxiety and insomnia. Moreover, this review proposes emerging therapeutic strategies utilizing engineered GABA-producing bacteria to target anxiety and insomnia, and highlights the potential of live biotherapeutics as novel interventions for mood disorders.